2022
DOI: 10.3390/vaccines10122021
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel N-Glycosylation Patterns Associated with the Emergence of New Genetic Variants of PRRSV-2 in the U.S

Abstract: Glycosylation of proteins is a post-translational process where oligosaccharides are attached to proteins, potentially altering their folding, epitope availability, and immune recognition. In Porcine reproductive and respiratory syndrome virus-type 2 (PRRSV-2), positive selection pressure acts on amino acid sites potentially associated with immune escape through glycan shielding. Here, we describe the patterns of potential N-glycosylation sites over time and across different phylogenetic lineages of PRRSV-2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…N-glycosylation pattern similarity parameter focuses on specific amino acid sites involved in potential glycan shielding, which is one immune evasion mechanism utilized by PRRSV-2 [74,75]. These sites have evolved under positive selection pressure [12,[76][77][78] and are believed to be associated with emergence at the sublineage level [7,79]. However, N-glycosylation pattern similarity was not significantly associated with a variant's success in any of our predictive models.…”
Section: Discussionmentioning
confidence: 91%
“…N-glycosylation pattern similarity parameter focuses on specific amino acid sites involved in potential glycan shielding, which is one immune evasion mechanism utilized by PRRSV-2 [74,75]. These sites have evolved under positive selection pressure [12,[76][77][78] and are believed to be associated with emergence at the sublineage level [7,79]. However, N-glycosylation pattern similarity was not significantly associated with a variant's success in any of our predictive models.…”
Section: Discussionmentioning
confidence: 91%
“…The positive selection site in GP5 can be driven by the host immune response (Music and Gagnon, 2010). In PRRSV-2, positive selection pressure acts on amino acid sites potentially associated with immune escape through glycan shielding [ 46 ]. Selection pressure analysis indicated that selection for situational diversification along the L1.8 (L1C) PRRSV phylogenetic tree was rare on the farms tested, regardless of vaccine use.…”
Section: Discussionmentioning
confidence: 99%
“…For each polymorphic amino acid site, serum-virus pairs were tabulated as 0 if they shared the same amino acid and 1 if they had a different amino acid at that site. We also scanned the genome for sites of potential N-glycosylation (31, 32) in the VP1 region using a custom-built R script. Pairs with identical sets of inferred glycosylated sites were coded as 0 and non-identical sets as 1.…”
Section: Methodsmentioning
confidence: 99%